2021
DOI: 10.1038/s41467-021-26251-6
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of human Pol κ bound to DNA and mono-ubiquitylated PCNA

Abstract: Y-family DNA polymerase κ (Pol κ) can replicate damaged DNA templates to rescue stalled replication forks. Access of Pol κ to DNA damage sites is facilitated by its interaction with the processivity clamp PCNA and is regulated by PCNA mono-ubiquitylation. Here, we present cryo-EM reconstructions of human Pol κ bound to DNA, an incoming nucleotide, and wild type or mono-ubiquitylated PCNA (Ub-PCNA). In both reconstructions, the internal PIP-box adjacent to the Pol κ Polymerase-Associated Domain (PAD) docks the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 94 publications
1
25
0
Order By: Relevance
“…For all reconstituted reactions, the median length of the reaction products at a particular timepoint was estimated using a modified version of the median analysis presented in refs. 15 , 88 . At each experimental timepoint, product intensities were integrated between the 1-nt SD (or NT) product and the top or bottom of the corresponding lane.…”
Section: Methodsmentioning
confidence: 99%
“…For all reconstituted reactions, the median length of the reaction products at a particular timepoint was estimated using a modified version of the median analysis presented in refs. 15 , 88 . At each experimental timepoint, product intensities were integrated between the 1-nt SD (or NT) product and the top or bottom of the corresponding lane.…”
Section: Methodsmentioning
confidence: 99%
“…In the eukaryotic replisome, when DNA is damaged, high-fidelity polymerases stall and the PCNA clamp, which is responsible for providing binding sites for the polymerases, is mono-ubiquitylated. This facilitates exchange of the replicative polymerase for a TLS polymerase and retention of TLS polymerase to the damaged sites ( Boehm et al, 2016 ; Lancey et al, 2021 ). These dynamics must be tightly regulated due to the low-fidelity of TLS polymerases.…”
Section: Protein Dynamics Provide Pathways For Lesion Bypassmentioning
confidence: 99%
“…The structural basis of the interaction of TLS polymerases with both DNA and unmodified or mono-ubitquitylated PCNA, and therefore the mechanism of TLS polymerase recruitment to sites of DNA damage, remain poorly understood. In 2021, Lancey et al (2021) identified this gap in knowledge and used cryo-EM to investigate.…”
Section: Cryo-electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…N-HelQ proteins did not bind to heparin, collecting in flow-through fractions. Purification of human DNA polymerase d complex (PolD1-4) was as described in [28], and DNA polymerase k (PolK) as in [34].…”
Section: Protein Purificationsmentioning
confidence: 99%